The repertoire of protein-sulfatide interactions reveal distinct modes of sulfatide recognition - Capelluto, Daniel G. S (Frontiers in Molecular Biosciences, 2022)
Sulfatide is an abundant glycosphingolipid in the mammalian nervous system, kidney, trachea, gastrointestinal tract, spleen, and pancreas and is found in low levels in other tissues. Sulfatide is characterized by the presence of a sulfate group in the hydrophilic galactose moiety, with isoforms differing in their sphingosine base and the length, unsaturation, and hydroxylation of their acyl chain. Sulfatide has been associated with a variety of cellular processes including immune responses, cell survival, myelin organization, platelet aggregation, and host-pathogen interactions. Structural studies of protein-sulfatide interactions markedly advanced our understanding of their molecular contacts, key-interacting residues, orientation of the sulfatide in its binding site, and in some cases, sulfatide-mediated protein oligomerization. To date, all protein-sulfatide interactions are reported to display dissociation constants in the low micromolar range. At least three distinct modes of protein-sulfatide binding were identified: (1) protein binding to short consensus stretches of amino acids that adopt -helical-loop--helical conformations; (2) sulfatide-bound proteins that present the sulfatide head group to another protein; and (3) proteins that cage sulfatides. The scope of this review is to present an up-to-date overview of these molecular mechanisms of sulfatide recognition to better understand the role of this glycosphingolipid in physiological and pathological states.